Building a model for measuring the level of physical and skill performance of volleyball players according to the variance level of the MCT1 gene and basic biochemical indicators - Alawadi, Basheer Shakir Hussein; Mutanish, Husam Hussein; Mutanish, Husam Hussein; Armoot, Alaa Kadhem; Aziz ASSafi, Asaad Adnan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The use of modern technology for scientific studies in a variety of sectors, including sports, has led to significant advancements and tremendous progress in this field. This has resulted in the best performance in various competitions and sports, and one of the modern technologies is the field of genetics technology. The aim of this study was to build a model for measuring the level of physical and skill performance of volleyball players according to the variance level of the MCT1 gene and basic biochemical indicators. The researchers used the descriptive approach. The sample of the study consisted of 21 advanced volleyball players from the Middle Euphrates region participating in the Men’s Premier League for the 2020-2021 sports season. To solve the research problem, we used the following variables: the MCT1 gene, chemical indicators of blood (LDH enzyme, the concentration of lactic acid in the blood, PH of blood), and the level of physical and skill performance in volleyball. The researchers used the Statistical Package for the Social Sciences (SPSS) for data analysis. In terms of the variance level of the MCT1 gene and various blood chemical indicators for the degree of performance of the skillful physical effort in volleyball, three prediction rates (models) were obtained. The amounts of variability of the MCT1 gene in the research sample varied between high and low levels. The researchers suggest using the model for prediction rates to determine the performance level of volleyball players and stressing genetic study of the MCT1 gene in volleyball players to facilitate the selection of players, particularly juniors.